2017
DOI: 10.4103/ijpvm.ijpvm_40_17
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chemotherapy-induced nephrotoxicity in children with cancer

Abstract: Children with cancer treated with cytotoxic drugs are frequently at risk of developing renal dysfunction. The cytotoxic drugs that are widely used for cancer treatment in children are cisplatin (CPL), ifosfamide (IFO), carboplatin, and methotrexate (MTX). Mechanisms of anticancer drug-induced renal disorders are different and include acute kidney injury (AKI), tubulointerstitial disease, vascular damage, hemolytic uremic syndrome (HUS), and intrarenal obstruction. CPL nephrotoxicity is dose-related and is ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 31 publications
(34 reference statements)
1
30
0
2
Order By: Relevance
“…In addition, the majority of renal tubules showed a cystically dilated lumen with flattening of their lining epithelial cells irrespective of unremarkably changed glycogen content observed within its lining cells. These findings coincided with those detected by Sharbaf et al who stated that the amount of oncotherapeutic drug in the tubular cells of the kidney exceeds several times its amount in the extracellular compartment and its major uptake occurs in the proximal renal tubules (24). In addition, Liao et al found a significant rise in both blood BUN and creatinine levels in the ischemic rat kidney at 4, 12 and 24 hours following renal reperfusion and they indicated a damage of the renal parenchymal tissue after reperfusion of ischemia so that the renal excretory capacity of urea nitrogen and creatinine was largely diminished (16).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, the majority of renal tubules showed a cystically dilated lumen with flattening of their lining epithelial cells irrespective of unremarkably changed glycogen content observed within its lining cells. These findings coincided with those detected by Sharbaf et al who stated that the amount of oncotherapeutic drug in the tubular cells of the kidney exceeds several times its amount in the extracellular compartment and its major uptake occurs in the proximal renal tubules (24). In addition, Liao et al found a significant rise in both blood BUN and creatinine levels in the ischemic rat kidney at 4, 12 and 24 hours following renal reperfusion and they indicated a damage of the renal parenchymal tissue after reperfusion of ischemia so that the renal excretory capacity of urea nitrogen and creatinine was largely diminished (16).…”
Section: Discussionsupporting
confidence: 91%
“…In clinics, chemotherapy for cancer patients is commonly based on the drug indications, recommended dosages, treatment duration, and adverse effects (e.g., nephrotoxicity and hepatotoxicity; Grossi et al, ; Sharbaf, Farhangi, & Assadi, ; Sulthana et al, ). Occasionally, it is difficult to prevent occurrences of adverse effects from chemotherapeutic drugs during therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Порушення функції нирок на тлі агресивного лікування та його наслідки: хронічна патологія нирок, розвиток ниркової недостатності, потреба у хронічному діалізі та трансплантації можуть призводити до відстрочення курсів лікування та зниження його ефективності [2][3][4]. Пацієнти з онкопатологією часто отримують нефротоксичні лікарські засоби (аміноглікозиди, ванкоміцин, амотерицин Б, нестероїдні протизапальні, алопуринол тощо), які можуть потенціювати ушкоджувальний вплив на нирки [5].…”
Section: оригінальні дослідженняunclassified
“…Відомо, що мелфалан належить до засобів, які можуть викликати гломерулярну дисфункцію [5,16,17]. Типовим побічним ефектом препарату є виражена мієлотоксичність [18].…”
Section: результати та їх обговоренняunclassified